2022
DOI: 10.1007/s10734-022-00873-1
|View full text |Cite
|
Sign up to set email alerts
|

Building a framework of a supportive pedagogical culture for teaching and pedagogical development in higher education

Abstract: The teaching and pedagogical development of academic communities is influenced by different contextual elements, which may not be apparent in everyday community practices, but may become evident through deeper reflection of the context. This study approaches these elements from the perspective of a supportive pedagogical culture for teaching and pedagogical development. The data consist of Finnish university teachers’ descriptions of teaching and its development in their work communities through thematic inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…For instance, Timperley (2008) showed that teacher development depends heavily on the organisational conditions that nurture professional learning and self-regulated inquiry. Myllykoski-Laine et al. (2022) asserted that academic development should be encapsulated in institutional norms, structures and discourses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, Timperley (2008) showed that teacher development depends heavily on the organisational conditions that nurture professional learning and self-regulated inquiry. Myllykoski-Laine et al. (2022) asserted that academic development should be encapsulated in institutional norms, structures and discourses.…”
Section: Discussionmentioning
confidence: 99%
“…That said, the transnational PDT at hand appears in line with scholarly efforts aimed to define the bold lines of any pedagogical-developmental initiative. The role of university administration is, thus, to offer helping hands to sustain such change and push it forward (Myllykoski-Laine et al, 2022). For example, university pedagogy centres may offer continuous consultation services for teachers to develop their teaching practices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This chapter joins a conversation that has been developing internationally, including Europe (Myllykoski-Laine et al, 2022), North America (Kenny et al, 2016;Newton et al, 2019;Wise et al, 2022;Wuetherick & Yu, 2016), the UK (McEwan, 2022;Webb & Tierney, 2020), Australia and Singapore (Myatt et al, 2018), South Africa (Boughey, 2011;Vithal, 2018), and New Zealand (Haigh et al, 2011). We believe a lens of self-reflection on our efforts to integrate SoTL within the fabric of an institution to be a worthwhile exercise to uncover the specifics of how "significant networks" and leadership operate within our context (Mårtensson et al, 2011;Roxå et al, 2008;Verwoord & Poole, 2016) and hope the insights generated can contribute to a growing understanding of institutionalization of SoTL in Higher Education.…”
Section: Institutionalization In Contextmentioning
confidence: 94%